For you and for me: creative experiences as gifts - Koronaki, Eirini; Kyrousi, Antigone G.; Zotou, Athina Y. (My University, 2018)
Contemporary consumers are increasingly valuing experiences over material possessions; experiences thus become desirable gifts. Simultaneously, the notion that creativity can result in substantial benefits for individuals has been gaining traction within the consumer behavior literature. In this context, it is proposed that creative experiences, namely the positive affective outcomes or hedonic benefits that stem from activities involving esthetic products, can be gifted. Esthetic products are hence seen as the means through which gifts of creative experiences are produced. Creative experiences can be gifted to a valued other, as an agapic love gift, celebrating the relationship and expressing the uniqueness of the receiver, and as a self-gift, spurred by the individual’s desire for self-actualization and eagerness to learn new things. The consequences in the context of the other-gift relate to strengthening the relationship between the two parties and representing the self for both the giver and the receiver, whereas in the self-gift context the consequences relate to notions of self-indulgence and self-expression.
Keywords: Creative experiences; Esthetic products; Gifts